Plano ótimo de exploração agropecuária e indicadores econômico-financeiros em área de aquífero aluvial no semiárido nordestino - Lins, Gleyciane Rodrigues (2023)
The exploitation of aquifers has been constantly growing due to the great demand for water, since in the semi-arid northeast the natural rainfall regime is irregularly distributed in time and space, thus requiring the optimization of this limited resource. The general aim of this research is therefore to determine the optimum agricultural exploitation plan, associated with estimates of economic and financial indicators for shrimp farming and rice farming activities with sustainable exploitation of the alluvial aquifer in the Morada Nova Irrigation Project (MNIP), as a way of supporting decision-making by producers. Specifically, it had the following objectives: 1. to build a linear programming model to maximize the producer's net income, based on the exploitable reserve of the alluvial aquifer for the MNIP; 2. to carry out an economic analysis of rice cultivation and shrimp farming in the MNIP. Data was obtained from research already carried out on the Irrigation Project and from information gathered from the Morada Nova Irrigated Perimeter Water Users Association. In addition, data was collected through questionnaires applied to irrigation farmers and shrimp producers. The questionnaires consisted of a set of quantitative variables related to the activities, with the aim of collecting information on the characteristics and production data for the year 2021. The economic viability of the producers was calculated and analyzed under deterministic conditions. The analysis of the optimization model included restrictions on the availability of land, the market, the exploitable groundwater reserve, the need for feed for cattle and areas with high percentages of exchangeable sodium. The results showed that the optimal occupation plan for the MNIP for the conditions of exploitation of groundwater resources in their potential condition, has a relevant importance in terms of the economic dimension, since 95% of the annual net revenue is associated with this activity. However, the sensitivity analysis of the water resource indicates that it is a limiting resource, which is reflected in the monthly occupation of the area at its most favorable in the months of February and March, with only 35% of the total project area. In the economic and financial analysis, these results allowed us to affirm that shrimp farming is a highly profitable activity, requiring a very high investment value in order to reach desirable levels of productivity, and has become an excluding activity for the vast majority of family-based irrigating farmers in the MNIP.